National survey of the injury prevention activities of sure start children's centres. (7th October 2012) - Watson, MC; Mulvaney, C; Kendrick, D; Stewart, J; Coupland, C; Hayes, M; Wynn, P; ,
Abstract : Background: Children's Centres were an important part of the UK Government's 10-year childcare strategy and were established across England to improve health outcomes for children. Injury prevention is one of the many roles Centres have in protecting and promoting children's health. The Centres have the potential to make significant contributions to home safety for children under 5. Aims/Objectives/Purpose: To ascertain what activities Children's Centres are undertaking to prevent or reduce unintentional injuries in the under fives. Methods: A postal questionnaire was sent to a sample of Children's Centre managers. Cluster sampling was used and 694 Centres were included in the sample. The questionnaire included questions on current activities, knowledge and attitudes to child injury prevention, child health priorities and partnership working. Results/Outcome: Responses were received from 56% of Centres. Most respondents (59%) did not know if there was an injury prevention group in their area, and 21% did not know if there was a local home safety equipment scheme. Only 11% knew the major cause of injury deaths in children under five. Lack of staff time and funding were seen as important barriers by staff to undertake injury prevention activities. There are considerable differences in the injury prevention activities between Children's Centres. There were gaps in knowledge both about injuries and local prevention initiatives. Significance/Contribution to the Field: This is the first study analysing the unintentional injury prevention activities of Children's Centres. They need support (including training and resources) if they are to fulfil their unintentional injury prevention roles.